STUDI TENTANG PERAN BUNDO KANDUANG DI NAGARI MUARO PANEH KABUPATEN SOLOK PROVINSI SUMATERA BARAT - Dira Afriani; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine how the role of Bundo Kanduang in Nagari Muaro Paneh, Solok Regency, West Sumatra Province. This research uses a qualitative approach. The informants who were examined using a purposive sampling technique were the head of the Bundo Kanduang Nagari Muaro Paneh and its members, Ninik Mamak, traditional observers, Wali Nagari Muaro Paneh and the community. Data collection techniques are carried out through observation, interviews, documentation and triangulation. With primary and secondary data sources. Data analysis tecniques by reduction, presentation and conclusions. Based on the results of research conducted, it can be concluded that the role of Bundo Kanduang currently shows the results of a role that plays well and even has increased in each of its roles, although there are still some roles of the Bundo Kandung that have not been well implemented and even experienced changes.Key Words: Role, Bundo Kanduang